Pharmacology of Radioiodinated Hexadecenoic Acid – A Myocardial Imaging Agent - Sun, Q.-X.; Zhang, J.; Ji, Q.-M.; Wang, Y.-C.; Xie, D.-F.; Hua, R.-L.; He, W.-Y.; Shi, X.-C.; Li, Y.-J.; Jiang, C.-J.; Dang, G.-F.; Zheng, H.-L.; Yang, Y.-F. (Nuklearmedizin - NuclearMedicine, 1984)
123I- and 131I-labeled hexadecenoic acid (IHDA, radiochemical purity over 92%, dissolved in 6% bovine serum albumin solution) was investigated in vivo. ICR mice were administered IHDA via the tail vein. Maximum myocardial uptake (27.3 ± 5.1%) was reached about 0.5 min after the injection. The ratio of uptake in the heart to that in the lungs was 2.3, to that in liver 1.5 and to that in other organs 2.4 to 6.4. The dog myocardium was visualized distinctly within 3-5 min with a gamma camera after i.v. 131I-IHDA, and not interfered with by activities in the lungs, liver and other organs. The low blood levels at 20 min had little effect on the quality of the heart images.